Sustainable development: an analysis from the Safe method - Pies, Willian; Gräf, Claudir Olípio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The following article comes through definitions of sustainable development its importance in the development of cities. These, in turn, need urgent a new model that makes them develop without affecting the environment. The term sustainability is being much discussed in political speeches, conferences, however, often are only in the speeches. It is believed that this discussion on sustainable development may come as a helper in future performances of developing cities.